Synthesis of cyclophosphamide metabolites by a peroxygenase from Marasmius rotula for toxicological studies on human cancer cells - Steinbrecht, Susanne; Kiebist, Jan; König, Rosalie; Thiessen, Markus; Schmidtke, Kai-Uwe; Kammerer, Sarah; Küpper, Jan-Heiner; Scheibner, Katrin (AMB Express, 2020)
Cyclophosphamide (CPA) represents a widely used anti-cancer prodrug that is converted by liver cytochrome P450 (CYP) enzymes into the primary metabolite 4-hydroxycyclophosphamide (4-OH-CPA), followed by non-enzymatic generation of the bioactive metabolites phosphoramide mustard and acrolein. The use of human drug metabolites as authentic standards to evaluate their toxicity is essential for drug development. However, the chemical synthesis of 4-OH-CPA is complex and leads to only low yields and undesired side products. In past years, fungal unspecific peroxygenases (UPOs) have raised to powerful biocatalysts. They can exert the identical selective oxyfunctionalization of organic compounds and drugs as known for CYP enzymes with hydrogen peroxide being used as sole cosubstrate. Herein, we report the efficient enzymatic hydroxylation of CPA using the unspecific peroxygenase from Marasmius rotula ( Mro UPO) in a simple reaction design. Depending on the conditions used the primary liver metabolite 4-OH-CPA, its tautomer aldophosphamide (APA) and the overoxidized product 4-ketocyclophosphamide (4-keto-CPA) could be obtained. Using a kinetically controlled approach 4-OH-CPA was isolated with a yield of 32% (purity > 97.6%). Two human cancer cell lines (HepG2 and MCF-7) were treated with purified 4-OH-CPA produced by Mro UPO (4-OH-CPA UPO ). 4-OH-CPA UPO –induced cytotoxicity as measured by a luminescent cell viability assay and its genotoxicity as measured by γH2AX foci formation was not significantly different to the commercially available standard. The high yield of 4-OH-CPA UPO and its biological activity demonstrate that UPOs can be efficiently used to produce CYP-specific drug metabolites for pharmacological assessment.